Examining Postdisaster Behavior Through a Criminological Lens: A Look at Property Crime. (July 2020) - Frailing, Kelly; Harper, Dee Wood
Disaster sociology has a rich and undeniably valuable history. Among other things, it has revealed much about the behavior of disaster survivors. In recent years, criminologists have turned their attention and the discipline's theories, methods, and data sources to understanding behavior in the wake of disasters and have come to a number of additional and sometimes different conclusions than did sociologists. In this article, we examine property crime in the wake of some recent and high-profile disasters. We find short-term increases in burglary after a number of disasters, ostensibly challenging some long-held notions in disaster sociology. We contend that the use of criminological methods including secondary analysis of extant data to understand behavior after disasters provides a more nuanced and accurate picture of postdisaster behavior and conclude with a call for inclusion of these theories, methods, and data sources in disaster studies more widely.